The Effect Of Promotion, Price, And Quality Of Service In Decision Making Using Online Transportation - Toni Yoyo; Georgius Listen (Komunitas Dosen Indonesia, 2020)
The results of the study show that the variables of promotion, price and service quality have a significant influence on decision making on online transportation. The equation Y = 5.709 + 0.072X1 - 0.022X2 + 0.845X3, which means that if there is an increase or decrease in promotion of 1 point, decision making will increase or decrease by 0.072 and if there is an increase or decrease in service quality by 1 point, decision making will experience an increase or decrease in service quality. increase or decrease by 0.022. And if there is an increase or decrease in the price of 1 point, the decision making will increase or decrease by 0.845. From the results of the analysis of the influence of promotion, promotion, service quality factors in making decisions using online transportation, it is known that promotion has a positive and strong correlation to decision-making that is equal to 0.739, price has a positive and strong correlation to decision-making of 0.654 and service quality has a correlation which is positive and very strong on decision making of 0.942. And the results of the coefficient of determination between promotion, price and service quality in decision making, it was found that promotions influenced decision making by 54.6%, the remaining 45.4% was influenced by other factors. promotions and prices affect decision making by 56.5%, the remaining 43.5% is influenced by other factors. and promotion, From the annova test, the Fcount for model 1 is 117.718 with a significant level of 0.000. Where the number 0.000 < 0.05 and also Fcount > Ftable or 117.718 > 3.09, thus ho is rejected and ha is accepted. From the annova test, Fcount for model 2 is 63.051 with a significant level of 0.000. Where the number 0.000 < 0.05 and also Fcount > Ftable or 63.051 > 3.09, thus ho is rejected and ha is accepted. From the results of the annova test, Fcount for model 3 is 265.552 with a significant level of 0.000. Where the number is 0.000 < 0.05 and also Fcount > Ftable or 265.552 > 3.09, thus ho is rejected and ha is accepted. This proves that there is a significant influence between promotion, price and service quality in making decisions using online transportation.